1995
DOI: 10.1002/jbm.820290216
|View full text |Cite
|
Sign up to set email alerts
|

Blood–biomaterial interactions in a flow system in the presence of bacteria: Effect of protein adsorption

Abstract: An in vitro continuous flow system with whole human blood was used to study blood-biomaterial interactions on a base polyurethane and three modified surfaces in the presence and absence of circulating Staphylococcus epidermidis. We hypothesized that the composition of the protein layer adsorbed on the surface of the biomaterial would influence the response of blood components and bacteria. We examined the test surfaces for adsorption of nine plasma proteins and adsorption profiles differed on the four surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Due to rapid kinetics, a layer of proteins adsorbs within seconds onto the surface of a material exposed to blood. Our studies show that in the presence of serum proteins, bacterial adhesion was minimal and independent of shear stress and surface chemistry effects which is in accordance with previously published data [5,[31][32][33]. An adsorbed protein layer may have concealed the surface characteristics of the material, thus, resulting in negligible effects of surface chemistry on adhesion trends.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Due to rapid kinetics, a layer of proteins adsorbs within seconds onto the surface of a material exposed to blood. Our studies show that in the presence of serum proteins, bacterial adhesion was minimal and independent of shear stress and surface chemistry effects which is in accordance with previously published data [5,[31][32][33]. An adsorbed protein layer may have concealed the surface characteristics of the material, thus, resulting in negligible effects of surface chemistry on adhesion trends.…”
Section: Discussionsupporting
confidence: 92%
“…3, Elasthane 90A-6F showed an overall slight increase in bacterial adhesion in the presence of serum, which is, however, <10% of bacterial adhesion observed in PBS. Diverse surface chemistries have been shown to produce varying patterns of adsorbed proteins [32,34]. Thus, in the presence of uorocarbon endgroups, the adsorbed protein layer may have increased attractive intermolecular forces, thereby promoting bacterial adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore hypothesized that an antifouling surface design that can prevent non-specific protein adsorption and cell attachment may be able to improve the performance of a range of biomedical devices. 1-6 For example, surface-induced thrombosis initiated by plasma protein adsorption, and the activation of the coagulation system, are major complications in blood-contacting devices (e.g. small-diameter, synthetic vascular grafts and cardiac valve prosthetics).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that activation or denaturation of adsorbed plasma proteins play a key role in the adhesion and activation of blood cells. 202,203 It was shown that signifi cant differences arise between adsorption patterns on heparin -coated and uncoated PVC surfaces. Fibronectin, fi brinogen, C3, and high -molecularweight kininogen ( HMWK ) exhibited specifi c adsorption profi les depending on the heparin coating of the surface.…”
Section: Reduction Of the Infl Ammatory Response By Increasingmentioning
confidence: 99%